The barrel modules of the ATLAS semiconductor tracker - Abdesselam, A; Akimoto, T; Allport, P; Alonso, J; Anderson, B; Andricek, L; Anghinolfi, F; Apsimon, R; Barbier, G; Barr, A; Batchelor, L; Bates, R; et al. (2006)
This paper describes the silicon microstrip modules in the barrel section of the SemiConductor Tracker (SCT) of the ATLAS experiment at the CERN Large Hadron Collider (LHC). The module requirements, components and assembly techniques are given, as well as first results of the module performance on the fully assembled barrels that make up the detector being installed in the ATLAS experiment. © 2006 Elsevier B.V. All rights reserved.